Electroacoustic Music and the Digital Future - Truax, Barry (Circuit, 2002)
This article outlines the author's views on the contemporary social and economic situation of electroacoustic music and digital technology in general. The dominance of commercial interests in shaping the listener, the artist, and the definition of culture is examined. Issues associated with digital technology, such as standardization, de-skilling, and upgrades, are discussed with respect to artistic practice. It is argued that marginalized artforms such as electroacoustic music have benefited from the windsurfer availability of the digital audio workstation (DAW) for production and the Internet for distribution, but no analogous avenue exists for the creation of the consumer.